The comprehension and production of Wh- questions among Malay children with developmental language disorders: Climbing the syntactic tree - Abu Bakar, Norsofiah; Smith, Giuditta; Razak, Rogayah A.; Garraffa, Maria (Frontiers in Psychology, 2022)
This study is an investigation of both comprehension and production of Wh-questions in Malay speaking children with a developmental language disorder (DLD). 15 Malay children with DLD (ages 7;0-9;11) were tested on a set of Wh- questions (Who subject and object, Which subject and object), comparing their performance with two control groups (15 age-matched children and 15 younger typically developing language-matched children). Malay children with DLD showed a clear asymmetry in comprehension of Wh-questions with a selective impairment for Which-NP questions compared to Who-questions. Age matched control performed at ceiling in all Wh-questions, while the language matched group reported a subject/object asymmetry selective for the Which-NP, as reported in other languages. In production both children with DLD and younger children had preference for the question with in-situ Wh elements, a structure allowed in colloquial Malay, but not produced by the age matched group. Several non-adult-like strategies were adopted by the children with DLD to avoid complex sentences, including substitution with Yes/No echo questions, production of the wrong Wh-question and use of a generic Wh element mana (Where). The study provides an insight on the development of Wh questions in both typical Malay children and children with DLD. Implications for the definition of a clinical marker for DLD in a free word language with Wh-in situ option will be discussed.